PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS III-A UPT. DI SD NEGERI 01 LIMO KAUM - Taruddin, Taruddin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study aims to improve student learning outcomes by applying the make a match cooperative learning model on the theme of Energy and Change in class III-A UPT. at SD Negeri 01 Limo Kaum. This type of research is a classroom action research (PTK) which is carried out in two cycles. The subjects of this study were students of class III-A UPT. in SD Negeri 01 Limo Kaum, amounting to 20 students. Data collection techniques used were observation, interviews, tests and documentation. The data obtained are in the form of observations as primary data, and learning outcomes tests as supporting data. The data analysis technique used is descriptive quantitative and qualitative. The results of this study indicate that the application of the cooperative learning model type make a match in thematic learning in class III-A UPT. at SD Negeri 01 Limo Kaum. From the data, the average student learning evaluation results increased, namely from the pre-cycle of 67.5 in the very poor category, increasing to 76.5 in the sufficient category in the first cycle, and increasing again to 85 with the very good category in the second cycle. This cycle stage states that student learning outcomes can increase due to applying the cooperative learning model make a match type.